ANALISIS DAMPAK PENGEMBANGAN PRODUK MAKANAN OLAHAN USAHA KECIL MIKRO TERHADAP KINERJA USAHA - Sunarso & Y. Djoko Suseno (Eksplorasi, 2008)
ABSTRACT This research aim to to know 1) conducted by product development execution is food proses small industry 2) affect product development to performance of effort with sale volume indicator 3) role of product development among other marketing mix factor which influence volume sale of food prosess small industry. In this research which become sampel is UKM maker / ketela flaky entrepreneur, tempe, banana, soybean cake fry and karak crisply in district of kartasura recent sukoharjo. Technique intake of sampel is simple random sampling. Used by research instrument is kuesioner weared to collect data about product development with transformation indicator, appetite, feel, and bale, hereinafter marketing mix with price indicator, distribution and promotion while performance of effort with sale volume indicator. Technique analyse used by data is descriptive analysis technique and doubled linear regression by using SPSS program 12.00 For Windows. Conclusion from research show there is positive influence of product development and marketing mix to performance effort of UKM posed at with equation Y=-2,051 + 0,470 XI + 0,600 X2 + e. By parsial there is influence which product development variable significant to UKM performance (t count = 3,701), and there is influence which marketing mix variable significant to UKM performance(t count=7,326). By together there is product development variable influence and marketing mix to performace effort of UKM (F count = 39,741). Variable product development and marketing mix give contribution equal to 68,2 percent to performance effort of UKM. Form result of this research can be given by suggestion to be able to UKM performance improving require to be generated by exiting potency in UKM x’self with motivating UKM through giving of given training continually. Keywords: Product development, marketing mix, performance effort of UKM.